Traditional food and its implications for development of rural tourism in Serbia - Stojanović, Žaklina; Ognjanov, Galjina; Filipović, Jelena (Economics of Agriculture, 2010)
Analysis is based on qualitative research. Two focus groups were conducted. Paper examines differences between urban and rural participants perception and image of traditional food and possible implications for rural tourism development. Analysis confrms positive image of traditional food both in rural and urban group. However, regarding perceptions several differences appear (in terms of variety, availability, home made or processed, quality control system and labeling) Authors argue that level of utilization of these concepts in further development of rural tourism will to a large extent depend on perceptions and image of fnal users of rural tourism services (urban population).